Lyrical Novel Genre Parodying in “Shaved Man” by A. Marienhof (Proceedings of Southern Federal University. Philology, 2018)
Ekaterina Yu. Belash (Rostov-on-Don, Russian Federation)The features of the genre poetics of the novel “Shaved Man” by A. Marienhof are analyzed. In the text, the features peculiar to lyrical prose are parodied, which is vividly represented at the levels of plot construction and points of view. Due to the game with the installation of confession and exploitation of the image of the clown (jester), a special parody-character of the hero’s self-disclosure is achieved. Of particular importance is the fragmentation of the novel: the inclusion of cultural and historical inserts, the choice of which often seems paradoxical, also underlines the game beginning in the treatment of the genre of lyrical novel.Key words: lyric prose, lyrical novel, Marienhof, parody, imagism, point of view.DOI 10.23683/1995-0640-2018-4-162-170